2007
DOI: 10.1002/gps.1782
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategy and risk of functional decline and mortality after nursing‐home acquired lower respiratory tract infection: two prospective studies in residents with dementia

Abstract: SUMMARYBackground Although lower respiratory tract infections (LRI) cause considerable morbidity and mortality among nursing home residents with dementia, the effects of care and treatment are largely unknown. Few large prospective studies have been conducted. Methods We pooled data from two large prospective cohort studies in 61 Dutch nursing homes and 36 nursing homes in the state of Missouri, United States. We included 551 US residents and 381 Dutch residents with dementia and LRI. Main outcome measures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Including discomfort at t0 in our analyses, we adjusted for a large number of potential confounders of associations of treatment with discomfort shortly before death. Post-hoc pooling of data of large observational studies has been shown to be a powerful method to detect treatment effects, including effects of type of antibiotic treatment on mortality [10,19,20]. The studies conducted were large and well representative of the Netherlands, but associations with antibiotics were assessed mainly in the context of the Pneumonia Study in the late 1990s, when few treatments were provided to relieve symptoms in the Netherlands [11] and also in the US [21].…”
Section: Discussionmentioning
confidence: 99%
“…Including discomfort at t0 in our analyses, we adjusted for a large number of potential confounders of associations of treatment with discomfort shortly before death. Post-hoc pooling of data of large observational studies has been shown to be a powerful method to detect treatment effects, including effects of type of antibiotic treatment on mortality [10,19,20]. The studies conducted were large and well representative of the Netherlands, but associations with antibiotics were assessed mainly in the context of the Pneumonia Study in the late 1990s, when few treatments were provided to relieve symptoms in the Netherlands [11] and also in the US [21].…”
Section: Discussionmentioning
confidence: 99%
“…At least 45% have musculoskeletal, genitourinary and/or ear, nose and throat disorders, with 48% of people at moderate stages and 69% at the severe stage of dementia having genitourinary disorders 3. Pneumonia is the leading cause of death with six month mortality rates reported at 36.4% to over 50% 4,5. These problems are discomforting and are associated with increased use of costly acute care services 6.…”
Section: Introductionmentioning
confidence: 99%
“…Medical comorbidities (e.g. dementia, pneumonia) have been used as predictors of mortality 9,10 but accurate measurement of comorbidities is hampered by different grades of severity of disease, multiplicity of diseases, and the interplay between various comorbidities 11,12 …”
Section: Introductionmentioning
confidence: 99%